Host cell species-specific effect of cyclosporine A on simian immunodeficiency virus replication - Takeuchi Hiroaki; Ishii Hiroshi; Kuwano Tetsuya; Inagaki Natsuko; Akari Hirofumi; Matano Tetsuro (Retrovirology, 2012)
Abstract Background An understanding of host cell factors that affect viral replication contributes to elucidation of the mechanism for determination of viral tropism. Cyclophilin A (CypA), a peptidyl-prolyl cis-trans isomerase (PPIase), is a host factor essential for efficient replication of human immunodeficiency virus type 1 (HIV-1) in human cells. However, the role of cyclophilins in simian immunodeficiency virus (SIV) replication has not been determined. In the present study, we examined the effect of cyclosporine A (CsA), a PPIase inhibitor, on SIV replication. Results SIV replication in human CEM-SS T cells was not inhibited but rather enhanced by treatment with CsA, which inhibited HIV-1 replication. CsA treatment of target human cells enhanced an early step of SIV replication. CypA overexpression enhanced the early phase of HIV-1 but not SIV replication, while CypA knock-down resulted in suppression of HIV-1 but not SIV replication in CEM-SS cells, partially explaining different sensitivities of HIV-1 and SIV replication to CsA treatment. In contrast, CsA treatment inhibited SIV replication in macaque T cells; CsA treatment of either virus producer or target cells resulted in suppression of SIV replication. SIV infection was enhanced by CypA overexpression in macaque target cells. Conclusions CsA treatment enhanced SIV replication in human T cells but abrogated SIV replication in macaque T cells, implying a host cell species-specific effect of CsA on SIV replication. Further analyses indicated a positive effect of CypA on SIV infection into macaque but not into human T cells. These results suggest possible contribution of CypA to the determination of SIV tropism.